Ternary polymerization retarder as well as preparation and application thereof

By preparing a terpolymer retarder made of 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid and polyimide, the cement slurry has short thickening time and large filtration loss in high temperature and high salt environments. Problem, stable application in deep well complex wells has been achieved.

CN119285866APending Publication Date: 2025-01-10CNPC GREATWALL DRILLING COMPANY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411326905.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art is difficult to provide a kind that can effectively extend the thickening time of cement slurry in high temperature and high salt environments, reduce filtration loss, and ensure the strength of cement stone, which is especially suitable for cementing construction of deep well complex wells.

Method used

Using terpolymer retarder prepared by polymerization of redox initiator by mixing 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid and polyimide in a specific mass ratio, adjust the pH value and at a specific temperature The terpolymer retarder was prepared by conducting the reaction.

Benefits of technology

The terpolymer retarder has high temperature resistance and high salt resistance, which extends the thickening time of cement slurry, reduces filtration loss, and shows versatility under the conditions of deep well complex wells, satisfying the complex wells of deep wells need.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005055658810000031
    Figure BDA0005055658810000031
  • Figure BDA0005055658810000041
    Figure BDA0005055658810000041
  • Figure BDA0005055658810000051
    Figure BDA0005055658810000051
Patent Text Reader

Abstract

The invention discloses a ternary polymerization retarder, which is prepared by polymerizing 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid and polyimide according to a mass ratio of (18 to 30): (27 to 30): (10 to 13). The invention also discloses a preparation method and application thereof. The ternary polymerization retarder provided by the invention has temperature resistance and salt resistance, also has an auxiliary effect on reducing the filter loss, and integrates multiple functions; and when the temperature is 240 DEG C or above, the oil-based drilling fluid has salt resistance, effectively prolongs the thickening time, assists in reducing the filter loss, and can meet the requirements of deep wells and complex wells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a ternary copolymer retarder and its preparation and application. Background Art

[0002] Research and practice of cementing technology in the past decade have shown that good cementing can increase oil and gas production by 5-10%. Using pure cement cementing alone can no longer meet the quality requirements of cementing construction. Therefore, according to the cement slurry hydration and hardening mechanism and the requirements of cement slurry performance in cementing operations, scientists and oil workers from all over the world have developed various types of oil well cement admixtures, such as retarders, fluid loss reducers, toughening agents, defoamers, dispersants, accelerators and early strength agents, in order to improve cement slurry performance, cement quality and oil recovery rate. Retarder is an admixture that can effectively delay the cement hydration reaction, thereby extending the setting time of cement slurry, facilitating cement pouring and improving work efficiency. At the same time, it will not have adverse effects on the various properties of cement stone in the later stage. It is one of the most important oil well cement admixtures. If the thickening time of cement slurry is too short, it may cause the cementing operation to be "sausage stuffing"; if the thickening time is too long, it may cause liquid channeling in the well and poor cementing quality, or casing falling off when re-drilling, and low early strength of cement stone. Therefore, a retarder resistant to ultra-high temperatures is needed, which is suitable for deep and complex wells. Summary of the invention

[0003] In view of the above problems, the present invention is proposed to provide a ternary copolymer retarder and a preparation method thereof that overcomes the above problems or at least partially solves the above problems.

[0004] As one aspect of the present invention, it relates to a ternary copolymer retarder, which is polymerized by AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) in a mass ratio of 18-25:27-30:10-13.

[0005] In certain specific embodiments, the oil well cement slurry retarder is polymerized under redox initiator conditions.

[0006] As another aspect of the present invention, it relates to a method for preparing the above-mentioned oil well cement slurry retarder, the method comprising:

[0007] (1) mixing 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid and polyimide in a mass ratio of 18-25:27-30:10-13 to obtain a monomer mixture;

[0008] (2) taking 100 parts of the above monomer mixture, adding it into 70-90 parts of water, adjusting the pH value to 6.5, and obtaining a monomer mixed solution;

[0009] (3) Then add the redox initiator.

[0010] In a specific embodiment, step (1) is preferably: (1) 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid and polyimide are mixed in a mass ratio of 25-30:30:13 to obtain a monomer mixture.

[0011] In a specific embodiment, in step (2), NaOH solution is preferably used to adjust the pH value.

[0012] In a specific embodiment, step (3) is preferably carried out at 70-80°C.

[0013] In a specific embodiment, the redox agent combination used by the redox initiator is ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of the ammonium persulfate and the ammonium ferrous sulfate hexahydrate are the same, which is 0.05-1.5 mol / L.

[0014] In a specific embodiment, the amount of the redox initiator is 0.85-0.95% of the mass of the monomer mixed solution.

[0015] As another aspect of the present invention, it relates to the application of the above-mentioned ternary copolymer retarder in oil and gas development.

[0016] As another aspect of the present invention, it relates to an oil well cement, wherein the oil well cement contains the above-mentioned ternary copolymer retarder.

[0017] As another aspect of the present invention, it relates to the application of the above-mentioned oil well cement in oil and gas development.

[0018] The ternary copolymer retarder provided by the present invention has no rigid groups, and the production batch is stable and not limited by time; the temperature resistance can be adjusted, and it has high temperature resistance and is suitable for medium and low temperatures; it has the function of assisting in reducing the filtration loss, realizing multi-functions in one. When the temperature is above 240°C, it has salt resistance, effectively prolongs the thickening time, assists in reducing the filtration loss, and can meet the needs of deep wells and complex wells. DETAILED DESCRIPTION

[0019] The parts referred to in this application are parts by mass unless otherwise specified.

[0020] Example 1: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=18:20:15 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 75 parts of water, and the pH value is adjusted to 6.5 with a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. The temperature is raised to 70°C and maintained for 4 hours while stirring to obtain a retarder.

[0021] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0022] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0023] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0024] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time, 48-hour strength test values ​​and water loss were recorded and entered into Table 1.

[0025] Table 1

[0026]

[0027] As shown in Table 1, the slurry could not be poured into the slurry cup of the viscometer, and the evaluation experiment could not be carried out. The retarder was incompatible with the cement. When the salt concentration increased, the slurry could not be poured into the slurry cup of the viscometer, and the evaluation experiment could not be carried out.

[0028] Example 2: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=18:20:15 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 80 parts of water, and the pH value is adjusted to 6.5 using a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. The temperature is raised to 70°C and maintained for 4 hours while stirring to obtain a retarder.

[0029] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0030] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0031] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0032] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time, 48-hour strength test values ​​and water loss were recorded and included in Table 2.

[0033] Table 2

[0034]

[0035] As shown in Table 2, the slurry cannot be poured into the thickener cup, and the evaluation experiment cannot be carried out. The retarder is incompatible with cement. When the salt concentration increases, the slurry cannot be poured into the thickener cup, and the evaluation experiment cannot be carried out.

[0036] Example 3: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=18:20:15 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 90 parts of water, and the pH value is adjusted to 6.5 with a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 70°C and maintained for 4 hours to obtain a retarder.

[0037] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0038] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0039] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0040] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time, 48-hour strength test values ​​and water loss were recorded and included in Table 3.

[0041] Table 3

[0042]

[0043] As shown in Table 3, the slurry could not be poured into the slurry cup of the viscometer, and the evaluation experiment could not be carried out. The retarder was incompatible with the cement. When the salt concentration increased, the slurry could not be poured into the slurry cup of the viscometer, and the evaluation experiment could not be carried out.

[0044] Example 4: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=18:20:15 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 80 parts of water, and the pH value is adjusted to 6.5 using a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 70°C and maintained for 4 hours to obtain a retarder.

[0045] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0046] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0047] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0048] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time, 48-hour strength test values ​​and water loss were recorded and included in Table 4.

[0049] Table 4

[0050]

[0051] As shown in Table 4, the slurry could not be poured into the thickener cup, and the evaluation experiment could not be carried out. The retarder was incompatible with cement. When the salt concentration increased, the slurry could not be poured into the thickener cup, and the evaluation experiment could not be carried out.

[0052] Example 5: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=18:20:15 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water, and the pH value is adjusted to 6.5 with a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate), wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. The temperature is raised to 70°C and maintained for 4 hours while stirring to obtain a retarder.

[0053] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0054] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0055] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0056] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time, 48-hour strength test values ​​and water loss were recorded and included in Table 5.

[0057] Table 5

[0058]

[0059] It can be seen from Table 5 that the slurry cannot be poured into the slurry cup of the viscometer, and the evaluation experiment cannot be carried out. The retarder is incompatible with cement. When the salt concentration increases, the slurry cannot be poured into the slurry cup of the viscometer, and the evaluation experiment cannot be carried out.

[0060] Example 6: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=20:25:40 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water, and the pH value is adjusted to 6.5 with a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. The temperature is raised to 70°C and maintained for 4 hours while stirring to obtain a retarder.

[0061] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0062] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0063] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0064] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time, 48-hour strength test values ​​and water loss were recorded and included in Table 6.

[0065] Table 6

[0066]

[0067] As shown in Table 6, the prepared retarder has the effect of extending the thickening time and also helps to reduce the filtration loss. However, when the salt concentration increases, the slurry cannot be poured into the thickener cup and the evaluation experiment cannot be carried out. This shows that the prepared retarder has temperature resistance but no salt resistance.

[0068] Example 7: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=20:20:45 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water, and the pH value is adjusted to 6.5 with a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. The temperature is raised to 70°C and maintained for 4 hours while stirring to obtain a retarder.

[0069] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0070] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0071] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0072] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time, 48-hour strength test values ​​and water loss were recorded and included in Table 7.

[0073] Table 7

[0074]

[0075] As shown in Table 7, the prepared retarder has the effect of extending the thickening time and also helps to reduce the filtration loss. However, when the salt concentration increases, the slurry cannot be poured into the thickener cup and the evaluation experiment cannot be carried out. This shows that the prepared retarder has temperature resistance but no salt resistance.

[0076] Example 8: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=20:15:15 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water, and the pH value is adjusted to 6.5 with a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. The temperature is raised to 70°C and maintained for 4 hours while stirring to obtain a retarder.

[0077] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0078] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0079] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0080] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time, 48-hour strength test values ​​and water loss were recorded and included in Table 8.

[0081] Table 8

[0082]

[0083] As shown in Table 8, the prepared retarder has the effect of prolonging the thickening time, but has no auxiliary effect on reducing the filtration loss. When the salt concentration increases, the slurry cannot be poured into the thickener cup, and the evaluation experiment cannot be carried out. This shows that the prepared retarder has temperature resistance but no salt resistance.

[0084] Example 9: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=20:25:25 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water, and the pH value is adjusted to 6.5 with a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. The temperature is raised to 70°C and maintained for 4 hours while stirring to obtain a retarder.

[0085] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0086] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0087] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0088] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time, 48-hour strength test values ​​and water loss were recorded and included in Table 9.

[0089] Table 9

[0090]

[0091] As shown in Table 9, the prepared retarder has the effect of extending the thickening time, and the comparison also helps to reduce the filtration loss. When the salt concentration increases, the slurry cannot be poured into the thickener cup, and the evaluation experiment cannot be carried out. This shows that the prepared retarder has temperature resistance but no salt resistance.

[0092] Example 10: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=20:22:25 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water, and the pH value is adjusted to 6.5 using a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. The temperature is raised to 70°C and maintained for 4 hours while stirring to obtain a retarder.

[0093] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0094] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0095] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0096] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time, 48-hour strength test values ​​and water loss were recorded and included in Table 10.

[0097] Table 10

[0098]

[0099]

[0100] As shown in Table 10, the prepared retarder has the effect of prolonging the thickening time, and the comparison also helps to reduce the filtration loss. When the salt concentration increases, the slurry cannot be poured into the thickener cup, and the evaluation experiment cannot be carried out. This shows that the prepared retarder has temperature resistance but no salt resistance.

[0101] Example 11: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=20:20:20 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water, and the pH value is adjusted to 6.5 with a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 70°C and maintained for 4 hours to obtain a retarder.

[0102] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0103] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0104] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0105] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time, 48-hour strength test values ​​and water loss were recorded and included in Table 11.

[0106] Table 11

[0107]

[0108] As shown in Table 11, the prepared retarder has the effect of extending the thickening time, which is also helpful to reduce the filtration loss. It also has the effect of extending the thickening time in semi-saturated salt water, which shows that the prepared retarder has both temperature resistance and salt resistance, but the strength value is low, and there is no strength value in semi-saturated salt water.

[0109] Example 12: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=18:27:13 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water, and the pH value is adjusted to 6.5 with a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 70°C and maintained for 4 hours to obtain a retarder.

[0110] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0111] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0112] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0113] Carry out the experiment at 240 degrees Celsius and 120mPa in accordance with Chapter 4 of SY / 5546-92, record the thickening time, 48-hour strength test value and water loss, and enter them in Table 12.

[0114] Table 12

[0115]

[0116] As shown in Table 12, the prepared retarder has the effect of prolonging the thickening time, but has no auxiliary effect on reducing the filtration loss. It also has the effect of prolonging the thickening time in semi-saturated salt water, indicating that the prepared retarder has both temperature resistance and salt resistance.

[0117] Example 13: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=20:28:10 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water to obtain a monomer mixed solution; the pH value of the above monomer mixed solution is adjusted to 6.5 with a NaOH solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. The temperature is raised to 70°C and maintained for 4 hours while stirring to obtain a retarder.

[0118] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0119] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0120] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0121] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time, 48-hour strength test values ​​and water loss were recorded and included in Table 13.

[0122] Table 13

[0123]

[0124] As shown in Table 13, the prepared retarder has the effect of prolonging the thickening time, and is also helpful in reducing the filtration loss. It also has the effect of prolonging the thickening time in semi-saturated salt water, but has no auxiliary effect on reducing the filtration loss, which shows that the prepared retarder has both temperature resistance and salt resistance, but has no auxiliary effect on reducing the filtration loss in semi-saturated salt water.

[0125] Example 14: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=23:29:11 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water, and the pH value is adjusted to 6.5 with a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 70°C and maintained for 4 hours to obtain a retarder.

[0126] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0127] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0128] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0129] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time, 48-hour strength test values ​​and water loss were recorded and included in Table 14.

[0130] Table 14

[0131]

[0132] As shown in Table 14, the prepared retarder has the effect of prolonging the thickening time, and is also helpful in reducing the filtration loss. It also has the effect of prolonging the thickening time in semi-saturated salt water, but has no auxiliary effect on reducing the filtration loss, which shows that the prepared retarder has both temperature resistance and salt resistance, but has no auxiliary effect on reducing the filtration loss in semi-saturated salt water.

[0133] Example 15: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=23:29:12 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water, and the pH value is adjusted to 6.5 with a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 70°C and maintained for 4 hours to obtain a retarder.

[0134] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0135] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0136] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0137] Carry out the experiment at 240 degrees Celsius and 120mPa in accordance with Chapter 4 of SY / 5546-92, record the thickening time, 48-hour strength test value and water loss, and enter them in Table 15.

[0138] Table 15

[0139]

[0140] As shown in Table 15, the prepared retarder has the effect of prolonging the thickening time, and is also helpful in reducing the filtration loss. It also has the effect of prolonging the thickening time in semi-saturated salt water, but has no auxiliary effect on reducing the filtration loss, indicating that the prepared retarder has both temperature resistance and salt resistance, but has no auxiliary effect on reducing the filtration loss in semi-saturated salt water.

[0141] Example 16: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=24:29:13 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water, and the pH value is adjusted to 6.5 with a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 70°C and maintained for 4 hours to obtain a retarder.

[0142] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0143] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0144] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0145] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time, 48-hour strength test values ​​and water loss were recorded and included in Table 16.

[0146] Table 16

[0147]

[0148] As shown in Table 16, the prepared retarder has the effect of prolonging the thickening time, and is also helpful in reducing the filtration loss. It also has the effect of prolonging the thickening time in semi-saturated salt water, indicating that the prepared retarder has both temperature resistance and salt resistance, and has an auxiliary effect on reducing the filtration loss.

[0149] Example 17: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=24:30:12 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water, and the pH value is adjusted to 6.5 with a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 70°C and maintained for 4 hours to obtain a retarder.

[0150] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0151] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0152] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0153] The experiment was carried out at 240 degrees Celsius and 120 mPa in accordance with Chapter 4 of SY / 5546-92. The thickening time, 48-hour strength test values ​​and water loss were recorded and included in Table 17.

[0154] Table 17

[0155]

[0156] As shown in Table 17, the prepared retarder has the effect of prolonging the thickening time, and is also helpful in reducing the filtration loss. It also has the effect of prolonging the thickening time in semi-saturated salt water, indicating that the prepared retarder has both temperature resistance and salt resistance, and has an auxiliary effect on reducing the filtration loss.

[0157] Example 18: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=25:30:13 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water, and the pH value is adjusted to 6.5 with a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.85% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 70°C and maintained for 4 hours to obtain a retarder.

[0158] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0159] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0160] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0161] Carry out the experiment at 240 degrees Celsius and 120mPa in accordance with Chapter 4 of SY / 5546-92, record the thickening time, 48-hour strength test value and water loss, and enter them in Table 18.

[0162] Table 18

[0163]

[0164]

[0165] As shown in Table 18, the prepared retarder has the effect of prolonging the thickening time, and is also helpful in reducing the filtration loss. It also has the effect of prolonging the thickening time in semi-saturated salt water, indicating that the prepared retarder has both temperature resistance and salt resistance, and has an auxiliary effect on reducing the filtration loss.

[0166] Example 19: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=25:30:13 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water, and the pH value is adjusted to 6.5 with a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 70°C and maintained for 4 hours to obtain a retarder.

[0167] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0168] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0169] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0170] Carry out the experiment at 240 degrees Celsius and 120mPa in accordance with Chapter 4 of SY / 5546-92, record the thickening time, 48-hour strength test value and water loss, and enter them in Table 19.

[0171] Table 19

[0172]

[0173] As shown in Table 19, the prepared retarder has the effect of prolonging the thickening time, and is also helpful in reducing the filtration loss. It also has the effect of prolonging the thickening time in semi-saturated salt water, indicating that the prepared retarder has both temperature resistance and salt resistance, and has an auxiliary effect in reducing the filtration loss.

[0174] Example 20: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=30:30:13 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water, and the pH value is adjusted to 6.5 using a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.1 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 70°C and maintained for 4 hours to obtain a retarder.

[0175] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0176] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0177] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0178] Carry out the experiment at 240 degrees Celsius and 120mPa in accordance with Chapter 4 of SY / 5546-92, record the thickening time, 48-hour strength test value and water loss, and enter them in Table 20.

[0179] Table 20

[0180]

[0181] It can be seen from Table 20 that the prepared retarder has the effect of prolonging the thickening time, and also has the effect of prolonging the thickening time in semi-saturated brine, which shows that the prepared retarder has both temperature resistance and salt resistance, and plays an auxiliary role in reducing the filtration loss.

[0182] Example 21: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=25:30:13 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 80 parts of water, and the pH value is adjusted to 6.5 using a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.15 mol / L, and the amount of the redox initiator is 0.90% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 75°C and maintained for 4 hours to obtain a retarder.

[0183] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0184] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0185] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0186] Carry out the experiment at 240 degrees Celsius and 120mPa in accordance with Chapter 4 of SY / 5546-92, record the thickening time, 48-hour strength test value and water loss, and enter them in Table 21.

[0187] Table 21

[0188]

[0189] It can be seen from Table 21 that the prepared retarder has the effect of prolonging the thickening time, and also has the effect of prolonging the thickening time in semi-saturated brine, which shows that the prepared retarder has both temperature resistance and salt resistance, and plays an auxiliary role in reducing the filtration loss.

[0190] Example 22: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=25:30:13 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 90 parts of water, and the pH value is adjusted to 6.5 using a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.05 mol / L, and the amount of the redox initiator is 0.95% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 75°C and maintained for 4 hours to obtain a retarder.

[0191] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0192] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0193] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0194] Carry out the experiment at 240 degrees Celsius and 120mPa in accordance with Chapter 4 of SY / 5546-92, record the thickening time, 48-hour strength test value and water loss, and enter them in Table 22.

[0195] Table 22

[0196]

[0197] It can be seen from Table 22 that the prepared retarder has the effect of prolonging the thickening time, and also has the effect of prolonging the thickening time in semi-saturated brine, which shows that the prepared retarder has both temperature resistance and salt resistance, and plays an auxiliary role in reducing the filtration loss.

[0198] Example 23: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=25:30:13 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 80 parts of water, and the pH value is adjusted to 6.5 using a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.15 mol / L, and the amount of the redox initiator is 0.90% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 80°C and maintained for 4 hours to obtain a retarder.

[0199] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0200] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0201] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0202] Carry out the experiment at 240 degrees Celsius and 120mPa in accordance with Chapter 4 of SY / 5546-92, record the thickening time, 48-hour strength test value and water loss, and enter them in Table 23.

[0203] Table 23

[0204]

[0205] It can be seen from Table 23 that the prepared retarder has the effect of prolonging the thickening time, and also has the effect of prolonging the thickening time in semi-saturated brine, which shows that the prepared retarder has both temperature resistance and salt resistance, and plays an auxiliary role in reducing the filtration loss.

[0206] Example 24: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=25:30:13 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 90 parts of water, and the pH value is adjusted to 6.5 using a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.05 mol / L, and the amount of the redox initiator is 0.95% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 70°C and maintained for 4 hours to obtain a retarder.

[0207] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0208] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0209] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0210] Carry out the experiment at 240 degrees Celsius and 120mPa in accordance with Chapter 4 of SY / 5546-92, record the thickening time, 48-hour strength test values ​​and water loss, and enter them in Table 24.

[0211] Table 24

[0212]

[0213] It can be seen from Table 24 that the prepared retarder has the effect of prolonging the thickening time, and also has the effect of prolonging the thickening time in semi-saturated brine, which shows that the prepared retarder has both temperature resistance and salt resistance, and plays an auxiliary role in reducing the filtration loss.

[0214] Example 25: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=25:30:13 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 70 parts of water, and the pH value is adjusted to 6.5 with a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.10 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 75°C and maintained for 4 hours to obtain a retarder.

[0215] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0216] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0217] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0218] Carry out the experiment at 240 degrees Celsius and 120mPa in accordance with Chapter 4 of SY / 5546-92, record the thickening time, 48-hour strength test value and water loss, and enter them in Table 25.

[0219] Table 25

[0220]

[0221] It can be seen from Table 24 that the prepared retarder has the effect of prolonging the thickening time, and also has the effect of prolonging the thickening time in semi-saturated brine, which shows that the prepared retarder has both temperature resistance and salt resistance, and plays an auxiliary role in reducing the filtration loss.

[0222] Example 26: AMPS (2-acrylamide-2-methylpropanesulfonic acid), AM (acrylic acid) and PI (polyimide) are mixed in a mass ratio of AMPS:AM:PI=25:30:13 to obtain a monomer mixture. 100 parts of the above monomer mixture are taken and put into 90 parts of water, and the pH value is adjusted to 6.5 using a NaOH solution to obtain a monomer mixed solution. Then a redox initiator is added, and the redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, wherein the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are both 0.10 mol / L, and the amount of the redox initiator is 0.93% of the mass of the above monomer mixed solution. While stirring, the temperature is raised to 80°C and maintained for 4 hours to obtain a retarder.

[0223] Performance evaluation: The cement-based slurry (blank control group) was: 500 g of G-grade cement + 300 g of quartz sand + 336 g of distilled water + 1.6% GWX-1L (produced by Great Wall Drilling and Cementing Company, an oil well cement defoamer) + 4% GWF-200L (produced by Great Wall Drilling and Cementing Company, an oil well cement fluid loss reducer).

[0224] 32 g of the retarder prepared in this example was added to the above cement-based slurry to form Experimental Group 1.

[0225] The distilled water in the cement-based slurry was replaced with 18% sodium salt water, and 32 g of the retarder prepared in this example was added to form Experimental Group 2.

[0226] Carry out the experiment at 240 degrees Celsius and 120mPa in accordance with Chapter 4 of SY / 5546-92, record the thickening time, 48-hour strength test value and water loss, and enter them in Table 26.

[0227] Table 26

[0228]

[0229]

[0230] It can be seen from Table 26 that the prepared retarder has the effect of prolonging the thickening time, and also has the effect of prolonging the thickening time in semi-saturated brine, which shows that the prepared retarder has both temperature resistance and salt resistance, and plays an auxiliary role in reducing the filtration loss.

[0231] By comparing the above examples, it can be seen that the retarders prepared in Examples 12-26 have both temperature resistance and salt resistance, and the preparation method is as follows:

[0232] (1) 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid and polyimide are mixed in a mass ratio of AMPS (2-acrylamide-2-methylpropane sulfonic acid): AM (acrylic acid): PI (polyimide) = (18-30): (27-30): (10-13) to obtain a monomer mixture;

[0233] (2) taking 100 parts of the above monomer mixture, adding it into 70-90 parts of water, adjusting the pH value to 6.5, and obtaining a monomer mixed solution;

[0234] (3) adding a redox initiator, wherein the redox initiator adopts a redox combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, the concentrations of ammonium persulfate and ammonium ferrous sulfate hexahydrate are the same, which is 0.05-1.5 mol / L, and the amount of the redox initiator is 0.85-0.95% of the mass of the above-mentioned monomer mixed solution; while stirring, heating to 70-80° C. and maintaining for 4 hours to obtain a retarder.

[0235] Furthermore, the retarder prepared in Examples 16-26 has both temperature resistance and salt resistance, and has a better auxiliary effect on reducing filtration loss. In the preparation method, step (1) is:

[0236] (1) 2-Acrylamide-2-methylpropanesulfonic acid, acrylic acid and polyimide were mixed in a mass ratio of AMPS (2-acrylamide-2-methylpropanesulfonic acid):AM (acrylic acid):PI (polyimide)=(24-30):(29-30):(12-13) to obtain a monomer mixture.

Claims

1. A ternary copolymer retarder, characterized in that: The ternary copolymer retarder is prepared by polymerizing 2-acrylamide-2-methylpropane sulfonic acid, acrylic acid and polyimide in a mass ratio of (18-30):(27-30):(10-13).

2. A method for preparing the ternary copolymer retarder according to claim 1, characterized in that: The method comprises: (1) mixing 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid and polyimide in a mass ratio of (18-30):(27-30):(10-13) to obtain a monomer mixture; (2) taking 100 parts of the above monomer mixture, adding it into 70-90 parts of water, adjusting the pH value to 6.5, and obtaining a monomer mixed solution; (3) Then add the redox initiator.

3. The method according to claim 2, characterized in that Step (1) is: mixing 2-acrylamide-2-methylpropanesulfonic acid, acrylic acid and polyimide in a mass ratio of (24-30):(29-30):(12-13) to obtain a monomer mixture.

4. The method according to claim 2, characterized in that In step (2), the pH value is adjusted using NaOH solution.

5. The method according to claim 2, characterized in that: Step (3) is carried out at 70-80°C.

6. The method of claim 2, characterized in that: The redox initiator uses a redox agent combination of ammonium persulfate-ammonium ferrous sulfate hexahydrate, and the concentrations of the ammonium persulfate and the ammonium ferrous sulfate hexahydrate are the same, which is 0.05-1.5 mol / L.

7. The method of claim 2, characterized in that The amount of the redox initiator used is 0.85-0.95% of the mass of the monomer mixed solution.

8. Use of the ternary copolymer retarder according to claim 1 in oil and gas development.

9. An oil well cement, characterized in that: The oil well cement contains the ternary copolymer retarder according to claim 1.

10. Use of the oil well cement according to claim 9 in oil and gas development.